Neural detection of changes in amplitude rise time in infancy. (April 2022) - Ní Choisdealbha, Áine; Attaheri, Adam; Rocha, Sinead; Brusini, Perrine; Flanagan, Sheila A.; Mead, Natasha; Gibbon, Samuel; Olawole-Scott, Helen; Williams, Isabel; Grey, Christina; Boutris, Panagiotis; Ahmed, Henna; et al.
Abstract: Amplitude rise times play a crucial role in the perception of rhythm in speech, and reduced perceptual sensitivity to differences in rise time is related to developmental language difficulties. Amplitude rise times also play a mechanistic role in neural entrainment to the speech amplitude envelope. Using an ERP paradigm, here we examined for the first time whether infants at the ages of seven and eleven months exhibit an auditory mismatch response to changes in the rise times of simple repeating auditory stimuli. We found that infants exhibited a mismatch response (MMR) to all of the oddball rise times used for the study. The MMR was more positive at seven than eleven months of age. At eleven months, there was a shift to a mismatch negativity (MMN) that was more pronounced over left fronto-central electrodes. The MMR over right fronto-central electrodes was sensitive to the size of the difference in rise time. The results indicate that neural processing of changes in rise time is present at seven months, supporting the possibility that early speech processing is facilitated by neural sensitivity to these important acoustic cues. Highlights: Mismatch responses to changes in amplitude rise time seen at seven and eleven months. Longitudinal data show a shift from positive MMR to negative MMN with age. The right fronto-central MMR is sensitive to the size of the change in rise time. Neurophysiological measurements show robust responses across a range of rise times.